‘A place for everyone who gets it’: - Charlotte Johanne Fabricius (Kvinder, Køn & Forskning)
This article discusses the political potential of sharing comics and cartoons on Instagram when that practice lies in the intersection of autobiographical art, feminist activism, and for-profit influencer work. Through a case study of cartoonist Mary Catherine Starr, aka @momlife_comics, and the 2022 viral campaign against her work known as ‘Peachgate,’ the article discusses whether Starr’s work participates in a juxtapolitical intimate public or whether it holds the potential to incite more radical transformation of the gender dynamics it criticizes. Investigating Starr’s visual style and aesthetic strategies, as well as the platformed visibility labor she engages in, the article argues that Peachgate can be seen as an indication of the potential for this work to transform from an intimate public to an affective public, although only if allowed to circulate beyond the intentions and preferred interpretations offered by Starr.